Illegal Financial Technology Practices in the Form of Online Loans Viewed from Business Ethics - Askana Fikriana; Suhendra (JUSTICES: Journal of Law, 2023)
The development of information technology has made it easier for people to obtain loans online. However, some online loan service providers are indicated to carry out illegal financial practices by providing loans without official permission and applying double interest. This practice raises ethical issues because it harms and burdens society. This study aims to analyze illegal technology financial practices in the form of online loans based on business ethics. The research uses qualitative methods with a literature study approach. The results showed that illegal technology financial practices are contrary to business ethics. Business actors must uphold the values of fairness, honesty, responsibility, and integrity. Cooperation between communities, businesses, and governments is needed to prevent this illegal practice.